JURIDICAL ANALYSIS OF INVESTIGATION IN THE CASE OF FORGIVENESS OF VACCINE CERTIFICATES BY POLICE INVESTIGATORS POLRESTA BARELANG - Bayu Septa, Anjas; P. Siadari, Lagat; Parameshwara, Parameshwara (RADJA PUBLIKA, 2022)
The construction of the journal topic above is: